PENGARUH KUALITAS PELAYANAN KARYAWAN TERHADAP KEPUASAN TAMU MENGINAP DI GRAND SERELA HOTEL YOGYAKARTA - Viviana Nur Azizah Amirullah; Yuliana Yuliana (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2023)
Abstract: This research was motivated by finding problems related to room occupancy rates that did not reach sales targets, employees who were not friendly with guests, guests who did not recommend the hotel, guests who did not want to visit the hotel again, employees who were not professional at work and employees who did not quickly respond to problems from guests. This study aims to analyze the effect of employee service quality on guest satisfaction staying at Grand Serela Hotel Yogyakarta. This research is included in the type of quantitative research using causal associative techniques. The population in the study was visitors staying at Grand Serela Hotel Yogyakarta. The respondents of this study amounted to 96 people obtained by non-probability sampling sample techniques with purposive sampling types. The research instrument used questionnaires arranged according to the Likert scale and by distributing questionnaires that had been prepared, then tested for validity and reliability first. The findings of the research lead to the following conclusions: The percentage (39.6%) shows the level of service quality is quite good. The percentage (29.2%) that indicates the level of satisfaction of guests staying is quite satisfied. The level of service quality provided by employees significantly affects the satisfaction of guests staying at Grand Serela Hotel Yogyakarta by 54.7% with other factors accounting for 45.3%.Keywords: Quality of Employee Service, Guest Stay Satisfaction